THE ROLE OF ABU ALI IBN SINO'S SPIRITUAL AND MORAL VIEWS IN THE DEVELOPMENT OF OUR COUNTRY (Scientific journal of the Fergana State University, 2025)
The article theoretically presents the ideas on the relevance of moral and educational issues in the works of Abu Ali ibn Sina for today. The implementation of educational work aimed at forming a new spiritual space and a new worldview based on the ideas of self-awareness and tolerance in the works of Ibn Sina, and raising them in a spirit of respect for the Islamic religion and philosophy, is of great importance. It is analyzed that the socio-moral education of young people and the formation of their social activity are defined as one of the important tasks of youth policy.